3D Switchable Diffractive Optical Elements Fabricated with Two‐Photon Polymerization. Issue 7 (20th February 2022) - Sandford O'Neill, John; Salter, Patrick; Zhao, Zimo; Chen, Bohan; Daginawalla, Hassan; Booth, Martin J.; Elston, Steve J.; Morris, Stephen M.
Abstract: Direct laser writing is demonstrated by two‐photon polymerization of multi‐element diffractive optical components that can be switched on and off with an applied voltage. By exploiting the 3D capabilities of the laser microfabrication technique, multiple diffractive optical elements are written into a single liquid crystal (LC) layer. The switching behavior of the diffractive optical elements is controlled by simply changing the write‐voltage of the anisotropic polymer structures during fabrication. Initially, 2D diffraction gratings are written at different depths within the LC layer. Each element is then activated by applying a voltage of sufficient amplitude that causes the second diffractive optical element to become inactive. This is then followed by a demonstration of multi‐element computer generated holograms that are written at different depths within the LC layer. By altering the magnitude of the applied voltage, different images/patterns can be observed in the replay field using a simple electrode configuration. These compact and transmissive LC optical components could excel in applications where a degree of switchability is required but a highly pixelated fully programmable device is excessive. Abstract : This paper demonstrates switchable multi‐component diffractive optical elements in polymerizable liquid crystal devices. These switchable elements have been fabricated at different depths within the liquid crystal layer using two‐photon polymerization direct laser writing. By changing the voltage amplitude applied to the liquid crystal device, different computer generated holograms can be accessed resulting in different images in the replay field.